2020
DOI: 10.1371/journal.pone.0227303
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of Actinidia chinensis in response to Botryosphaeria dothidea infection

Abstract: Ripe rot caused by Botryosphaeria dothidea causes extensive production losses in kiwifruit (Actinidia chinensis Planch.). Our previous study showed that kiwifruit variety "Jinyan" is resistant to B. dothidea while "Hongyang" is susceptible. For a comparative analysis of the response of these varieties to B. dothidea infection, we performed a transcriptome analysis by RNA sequencing. A total of 305.24 Gb of clean bases were generated from 36 libraries of which 175.76 Gb was from the resistant variety and 129.48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
3
9
0
Order By: Relevance
“…This result was consistent with previously reported that maturity-stage fruits were associated with susceptibility to suffering abiotic and biotic influence (Buron-Moles et al, 2015). The importance of biodiversity to ecosystem functioning is well recognized (Wang et al, 2020a(Wang et al, , 2020b. Changes that occur in the microbial community of host tissues can potentially have a significant effect on the health of the host plant (Wisniewski & Droby, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result was consistent with previously reported that maturity-stage fruits were associated with susceptibility to suffering abiotic and biotic influence (Buron-Moles et al, 2015). The importance of biodiversity to ecosystem functioning is well recognized (Wang et al, 2020a(Wang et al, , 2020b. Changes that occur in the microbial community of host tissues can potentially have a significant effect on the health of the host plant (Wisniewski & Droby, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The disease index for the four pathogens was calculated on kiwifruit and results indicated that the disease index was >40% at 10 dpi (Figure 2). Notably, the appearance and development of the decay lesions differed among the four different processes, which is consistent with previous studies with other postharvest pathogens (Toju et al, 2018;Wang et al, 2020aWang et al, , 2020bZhu et al, 2022). Meanwhile, our result also revealed that the four identified pathogens also infected mature kiwifruit and the infection time and disease incidence were much faster and higher than that during in infection process of development of kiwifruit (Figure 2B and Figure 6F).…”
Section: Discussionsupporting
confidence: 91%
“…Bioinformatic analysis indicated that the target genes of up-regulated lncRNAs were enriched in the activation of innate immune responses, defense responses to bacteria, immune system processes, plant hormone signal transduction, phenylpropanoid biosynthesis, and other pathways [10] . Previous studies have also analyzed the transcriptome of infected kiwifruit [17] , [18] . Wang et al conducted a transcriptome analysis of kiwifruit infected with Pseudomonas syringae , and identified a number of lncRNAs related to the regulation of various plant defense processes, including innate immune response, systemic-acquired resistance, and salicylic acid-mediated defense [19] .…”
Section: Discussionmentioning
confidence: 99%
“…'Hongyang' is one of the main kiwifruit varieties cultivated in Jiangxi province, and the whole genome sequencing has been completed (Yue et al, 2020). 'Hongyang' kiwifruit was selected as the tested fruit based on its high sensitivity to B. dothidea (Wang et al, 2020b). At maturity, kiwifruit were harvested from an orchard (28.…”
Section: Fruitmentioning
confidence: 99%